PENGARUH KEPEMIMPINAN CAMAT DAN DISIPLIN PEGAWAI TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN PULAU BURUNG KABUPATEN INDRAGIRI HILIR - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
The purpose of this study is to describe the leadership of the sub-district head and the discipline of the employee's influence on the performance of the employees of the Pulau Burung sub-district, Indragiri Hilir Regency. The results showed that for the subdistrict leadership variable obtained a significance level of 0,000 <0.05, the hypothesis was accepted. Therefore the sub-district leadership has a partial effect on employee performance. Employee discipline of the significance level of 0,000 <0.05, the hypothesis is accepted. Therefore employee discipline has a partial effect on employee performance. F test results obtained a significance level of 0,000 <0.05 then the hypothesis is accepted. This means that the sub-district leadership and employee discipline simultaneously have a positive and significant effect on employee performance. The results of the coefficient of determination test indicate that the influence of sub-district leadership and employee discipline variables on employee performance by 52%, while the remaining 48% can be explained by other variables outside of the research variables.